Regions of multistationarity in cascades of Goldbeter–Koshland loops - Giaroli, Magalí Paola (2019)
We consider cascades of enzymatic Goldbeter-Koshland loops (Goldbeter and Koshland in Proc Natl Acad Sci 78(11):6840-6844, 1981) with any number n of layers, for which there exist two layers involving the same phosphatase. Even if the number of variables and the number of conservation laws grow linearly with n, we find explicit regions in reaction rate constant and total conservation constant space for which the associated mass-action kinetics dynamical system is multistationary. Our computations are based on the theoretical results of our companion paper (Bihan, Dickenstein and Giaroli 2018, preprint: arXiv:1807.05157) which are inspired by results in real algebraic geometry by Bihan et al. (SIAM J Appl Algebra Geom, 2018).